(untitled) (Scientific journal of the Fergana State University, 2024)
By processing local raw materials Navbakhor bentonite with the salts of calcium, zinc and magnesium, zeolite with a composition of / was prepared in laboratory conditions. The sorption capabilities of zeolites prepared from local raw materials were studied and a technological scheme was developed by adding metal salts to the sorbent and subsequent heat treatment. A / catalyst based on zeolite sorbents has been developed for drying oil and natural gas from water vapor and removing sulfur compounds, their texture and sorption properties have been studied. During X-ray diffraction analysis of the surface of the / catalyst, the total amount of the ionic phase Ca2+, Zn2+ and Mg2+ was studied. At JSC "UZBEKGAZ" - Mubarek gas processing plant, experimental tests were carried out to study the sorption properties of this catalyst, with the comparative sorption of sulfides with the participation of /. The sorption properties of HSZ catalysts have been studied. Experimental tests of the CaA(5A) catalyst were carried out for comparison, which showed hydrogen sulfide absorption equal to 8.2% by weight, and our developed catalyst / with a total capacity of 14.3% by weight.